Developing critical thinking, creativity, collaboration, and communication skills through islamic education: A study at sd negeri 78 bengkulu city - Yarsi Putri; Meldiana; Fahrozi Ahmad; Andre Taulani; Yosi Yulizah (Amorti: Jurnal Studi Islam Interdisipliner, 2025)
21st-century skills are essential competencies that students must possess to face the development of science, technology, and the dynamics of global life. One of the skills focused on in 21st-century learning is the 4C skills, which include critical thinking, creativity, collaboration, and communication. This study aims to describe teacher strategies in developing 4C skills in students at SD Negeri 78, Bengkulu City. The study used a qualitative approach with descriptive methods. The research subjects consisted of the principal, class teachers, and students. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis used the Miles, Huberman, and Saldaña model, which includes data reduction, data presentation, and conclusion drawing. The results showed that teachers developed critical thinking skills through problem-based learning and providing contextual questions. Creativity skills were developed through project activities, making works, and utilizing digital media. Collaboration skills were developed through group discussions, teamwork, and project-based learning, while communication skills were developed through presentations, class discussions, questions and answers, and speaking activities in front of the class. Supporting factors included the support of the principal, teacher competence, the availability of learning resources, student enthusiasm, and school programs that support project-based learning. Inhibiting factors include differences in student academic ability, limited learning time, low self-confidence among some students, limited use of technology, and lack of parental learning support. This study concludes that teacher strategies play a crucial role in developing students' 4C skills, thereby supporting active, creative, collaborative, and communicative 21st-century learning.